Diversity of natural yeast flora of grapes and its significance in wine making - Deshpande, M.V.; Mane, S.S.; Ghormade, V.; Tupe, S.G. (Yeast Diversity in Human Welfare, 2017)
The biodiversity of yeasts associated with grapes has been studied in different regions of wine producing countries throughout the world. Most of the species associated with the wine environment are similar, while some species are specifically associated with specific regions. Though Saccharomyces cerevisiae is primarily used for fermentation of grape juice, its occurrence is low on grape berries. Non-Saccharomyces yeasts belonging to the genera Torulaspora, Hanseniaspora, Pichia, Candida, Issatchenkia, Metschnikowia etc. are in abundance in grape musts and may dominate the early stages of fermentation. Subsequently, S. cerevisiae proliferates, becomes dominant and completes the wine fermentation. Therefore, yeasts diversity associated with the grapes and must significantly contribute to the quality and varietal character of wine. In present review, the diversity of yeasts associated with vineyard, winery, succession of yeasts during fermentation and their role in wine quality is discussed. The knowledge will be useful to monitor and control the fermentation with respect to quality and spoilage.

Fungal differentiation: a model phenomenon to screen antifungal drugs - Pathan, E.K.; Tupe, S.G.; Deshpande, M.V. (Developments in Fungal Biology and Applied Mycology, 2017)
Pathogenic fungi change the morphology to a suitable vegetative form such as unicellular yeast or filamentous mycelium for the survival and proliferation in the host as well as to defeat cellular and physiological defences of the host. The microenvironment of the pathogen triggers different biochemical processes finally leading to differentiation. These biochemical processes, which correlate with morphological change from saprophytic/less virulent to pathogenic form, can be targeted for the development of novel antifungal agents. The present chapter deals with the role of differentiation in fungal pathogenesis and discusses different biochemical events as target for the antifungal strategies.